Comparative Genomic Hybridization: DNA preparation for microarray fabrication - Redon, Richard (2009)
The spatial resolution of microarray-based comparative genomic hybridization (array-CGH) is dependent on the length and density of target DNA sequences covering the chromosomal region of interest. Here we describe the methods developed at the Wellcome Trust Sanger Institute (Cambridge, UK) to construct microarrays composed of large-insert clones available through genome sequencing projects. These methods are applicable to Bacterial and Phage Artificial Chromosomes (BAC and PAC) as well as fosmid and cosmid clones. The protocols are scalable for the construction of microarrays composed of several hundreds up to several ten thousands clones.